Enlaces - Becker Ravest, Alex (AUS - Arquitectura / Urbanismo / Sustentabilidad, 2017)
http://www.gdrc.org/uem/planning/urban-planning.html http://www.sustainablemeasures.com/index.html http://www.urban.uiuc.edu/Projects/ucgis/index1.htm http://home.versatel.nl/alolar/a4iu/blogs.htm http://www.arquitecturaenfardos.cl http://www.corrim.org